1996
DOI: 10.1095/biolreprod55.4.895
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Withdrawal Promotes Stage-Specific Detachment of Round Spermatids from the Rat Seminiferous Epithelium1

Abstract: Testosterone (T) has been shown to be essential for the completion of spermiogenesis. Our previous studies showed that when intratesticular T was suppressed for 11 wk, the conversion of round spermatids between stages VII and VIII of the spermatogenic cycle was markedly suppressed and that elongated spermatids were undetectable. The fate of the round spermatids that did not proceed through this conversion was unclear. The current study aimed to investigate this T-dependent loss of round spermatids during stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
2
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 37 publications
10
143
2
2
Order By: Relevance
“…In this report, an in vivo model using Adjudin was used to induce AJ restructuring in the testis without damaging the BTB (12). It is unlikely that the changes reported here are the result of a drug toxicity effect of Adjudin toward junctions, because many of the biochemical changes in the seminiferous epithelium, such as an induction of protein and lipid kinases, phosphatases, adaptors, and AJ-integral membrane proteins, that are associated with the event of germ cell depletion from the epithelium have been reproduced and validated (14,23,28) by using an intratesticular testosterone suppression model (29,30). Furthermore, a more recent study has illustrated that an AJ restructuring event in the testis can indeed be limited to the apical ES without compromising the BTB (14), consistent with data obtained from the Adjudin model (12).…”
Section: Discussionmentioning
confidence: 83%
“…In this report, an in vivo model using Adjudin was used to induce AJ restructuring in the testis without damaging the BTB (12). It is unlikely that the changes reported here are the result of a drug toxicity effect of Adjudin toward junctions, because many of the biochemical changes in the seminiferous epithelium, such as an induction of protein and lipid kinases, phosphatases, adaptors, and AJ-integral membrane proteins, that are associated with the event of germ cell depletion from the epithelium have been reproduced and validated (14,23,28) by using an intratesticular testosterone suppression model (29,30). Furthermore, a more recent study has illustrated that an AJ restructuring event in the testis can indeed be limited to the apical ES without compromising the BTB (14), consistent with data obtained from the Adjudin model (12).…”
Section: Discussionmentioning
confidence: 83%
“…The normal fertility exhibited by stressed males may be explained by the fact that forced swimming lasted 15 days, a period shorter than the 48-to 53-day duration of one cycle of the seminiferous epithelium. Previous studies have shown that long-term testosterone suppression led to reduced spermatogonial and spermatocyte production, and that losses during these earlier stages of germ cell development led to reduction in the spermatid population (18). When intratesticular testosterone was suppressed for 11 weeks, the conversion of round spermatids from stage VII to stage VIII was markedly suppressed and elongated spermatids were not detected.…”
mentioning
confidence: 91%
“…Terganggunya fungsi sel Sertoli menyebabkan sekresi androgen binding protein (ABP), suplai nutrien, growth factors, laktat, dan transferin juga terganggu, sehingga mengakibatkan proses spermatogenesis akan terganggu, karena zat tersebut sangat dibutuhkan dalam proses spermatogenesis (Lohiya et al, 2002). Selain itu, hilangnya fungsi sel Leydig menyebabkan sekresi hormon testosteron menjadi rendah, sehingga proses spermiogenesis menjadi terganggu (Donnel et al, 1996). Senyawa aktif tanin diduga berperanan dalam menurunkan jumlah sel spermatid.…”
Section: Hasil Dan Pembahasan Efek Ekstrak Daun Pegagan (Centella Asiunclassified